IMPLEMENTASI KEBIJAKAN ABSEN ELEKTRONIK (E-ABSENSI BNI INNOVATION) BERPENGARUH TERHADAP KINERJA PEGAWAI PADA DIVISI JAKARTA COLLECTIONMANAGEMENT PADA PT. BANK NEGARA INDONESIA 1946 (PERSERO) Tbk, JAKARTA-BARAT - Irvan Arif Kurniawan; Hilman .; Indri Lestari (UNIVERSITAS ISLAM SYEKH YUSUF, 2019)
This journal entitled Implementation of Electronic Absence Policy (BNI E-Attendance Innovation) Affects Employee Performance in the Jakarta Division of Collection Management at PT. Bank Negara Indonesia 1946 (Persero) Tbk, West Jakarta ”. The population in this study are employees who work at PT. Bank Negara Indonesia 1946 (persero) Tbk, West Jakarta, which measured 222 people, from which the researcher used 69 people as samples to be tested. The research method used in this research is the associative method, the data technique used is literature study and field study through observation and questionnaires. Furthermore, it is tested by quantitative analysis using a proportional stratified random sampling technique, and data processing using the SPSS (Product and Solution Service) program. Keyword: Implementation, E-Attendance, the performance